HPLC‐MS/MS analysis of anthocyanins in human plasma and urine using protein precipitation and dilute‐and‐shoot sample preparation methods, respectively. (30th January 2018) - Liu, Junguo; Song, Jiuxue; Huang, Karen; Michel, Deborah; Fang, Jim
Abstract: A high‐performance liquid chromatography tandem–mass spectrometry (HPLC‐MS/MS) method has been developed to analyze anthocyanins in urine and plasma to further understand their absorption, distribution, metabolism and excretion. The method employed a Synergi RP‐Max column (250 × 4.6 mm, 4 μm) and an API 4000 mass spectrometer. A gradient elution system consisted of mobile phase A (water–1% formic acid) and mobile phase B (acetonitrile) with a flow rate of 0.60 mL/min. The gradient was initiated at 5% B, increased to 21% B at 20 min, and then increased to 40% B at 35 min. The analysis of anthocyanins presents a challenge because of the poor stability of anthocyanins during sample preparation, especially during solvent evaporation. In this method, the degradation of anthocyanins was minimized using protein precipitation and dilute‐and‐shoot and sample preparation methods for plasma and urine, respectively. No interferences were observed from endogenous compounds. The method has been used to analyze anthocyanin concentrations in urine and plasma samples from volunteers administered saskatoon berries. Cyanidin‐3‐galactoside, cyanidin‐3‐glucoside, cyanidin‐3‐arabinoside, cyanidin‐3‐xyloside and quercetin‐3‐galactoside, the five major flavonoid components in saskatoon berries, were identified in plasma and urine samples.